2007
DOI: 10.1136/oem.2006.031005
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study of chrysotile textile workers: cohort mortality and exposure-response

Abstract: Objectives: This report provides an update of the mortality experience of a cohort of South Carolina asbestos textile workers. Methods: A cohort of 3072 workers exposed to chrysotile in a South Carolina asbestos textile plant (1916-77) was followed up for mortality through 2001. Standardised mortality ratios (SMRs) were computed using US and South Carolina mortality rates. A job exposure matrix provided calendar time dependent estimates of chrysotile exposure concentrations. Poisson regression models were fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
183
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(193 citation statements)
references
References 22 publications
(24 reference statements)
8
183
0
2
Order By: Relevance
“…The estimate of K L with α = 1 is 0.030 (f-yr/ml) −1 , 90% CI: (0.023, 0.037), and the estimate with α variable (α = 1.35) is K L = 0.018 (f-yr/ml) −1 , 90% CI: (0.011, 0.027). Hein et al (2007) reported three deaths from mesothelioma, and Hein graciously identified these for us in the data files. Applying the method described in the main article for calculating K M from raw data, the following estimate was obtained:…”
Section: South Carolina Textile Factorymentioning
confidence: 99%
See 2 more Smart Citations
“…The estimate of K L with α = 1 is 0.030 (f-yr/ml) −1 , 90% CI: (0.023, 0.037), and the estimate with α variable (α = 1.35) is K L = 0.018 (f-yr/ml) −1 , 90% CI: (0.011, 0.027). Hein et al (2007) reported three deaths from mesothelioma, and Hein graciously identified these for us in the data files. Applying the method described in the main article for calculating K M from raw data, the following estimate was obtained:…”
Section: South Carolina Textile Factorymentioning
confidence: 99%
“…For studies conducted at the same facility (generally among highly overlapping cohorts), a single study was selected for presentation in Figure 11. Thus, for South Carolina, the Hein et al (2007) study was selected because this study includes the most recent follow-up and because of access to the raw data for this study. Similarly, the Sullivan (2007) study was selected to represent the Libby vermiculite site over the other studies at this facility (McDonald et al, 1986;.…”
Section: Lung Cancer Potency Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors noted there were several other death certificates which mentioned 'cancer of the abdomen' however, no autopsy or other confirmatory data were available. Further description and follow-up of this South Carolina chrysotile asbestos textile worker cohort [40] expanded the numbers of workers to 3072 and found three cases of mesothelioma including the specification that the one peritoneal case was a female case.…”
Section: Occupational Cohortsmentioning
confidence: 99%
“…The 2014 Helsinki report (1) states on pages 6 and 7: "Using an estimate of 4% increase of risk for each fibres per cubic centimeter per year (fibre year) of cumulative exposure: 'A cumulative exposure of 25 fibre-years is estimated to increase the risk of lung cancer 2-fold, clinical cases of asbestosis may occur at comparable cumulative exposures." Setting aside the fact that published studies support a linear dose-response relationship without a threshold (24)(25)(26)(27), the 2014 consensus statement ignores its previously acknowledged range of risk estimates and chooses the upper end of the range without comment or explanation. This compounds the error of its failure to acknowledge and reference studies indicating a linear dose-response relationship and instead embraces a statement that implicates a specific threshold.…”
Section: Letter To the Editormentioning
confidence: 99%